2019
DOI: 10.1002/esp.4704
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic and hydrological controls on groundwater dolocrete formation in the semi‐arid Hamersley Basin, northwest Australia

Abstract: Groundwater dolocretes may exert an important geomorphic control on landscape evolution within sub‐humid to arid regions. However, the geomorphic and hydrogeological settings of dolocrete remain poorly described. The hydrochemical conditions of dolomite precipitation in groundwater environments are also not well known. Classic models of dolocrete formation explain dolomite precipitation from highly evolved groundwaters at the terminus of major drainage but do not explain dolocrete distributed in regionally ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 84 publications
(207 reference statements)
0
39
0
Order By: Relevance
“…In both cases, dolocrete formation is suggested to be stimulated by more saline evaporitic paleoenvironmental conditions, possibly playa lakes or saline mudflats, as evidenced by δ 18 O values. Interestingly, the most recent study observed extensive fossilized EPS and organic filaments in more shallow sections of the same cores 74 indicating a possible presence of microbial mats at the dolomite forming locations, even though no information about microbial composition exists. The paleoenvironment in which this occurred looks remarkably resembles the Khor Al-Adaid sabkha.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In both cases, dolocrete formation is suggested to be stimulated by more saline evaporitic paleoenvironmental conditions, possibly playa lakes or saline mudflats, as evidenced by δ 18 O values. Interestingly, the most recent study observed extensive fossilized EPS and organic filaments in more shallow sections of the same cores 74 indicating a possible presence of microbial mats at the dolomite forming locations, even though no information about microbial composition exists. The paleoenvironment in which this occurred looks remarkably resembles the Khor Al-Adaid sabkha.…”
Section: Discussionmentioning
confidence: 95%
“…Another very recent study on the same post-glacial dolostone cap rocks discovered enrichment of newly identified biomarker 25,28-bisnorgammacerane (25,28-BNG) which can be formed as a result of a transition of microbial mat dominated by cyanobacteria to one dominated by heterotrophs 72 . Further paleo-evidence for the proposed mechanism facilitating low-t dolomite formation comes from studies that examined dolocretes were formed within the Hammersley Basin during the quaternary age (37 to > 45 ka) and Late Miocene and Pliocene (5.3–3.5 ma) 73 , 74 . In both cases, dolocrete formation is suggested to be stimulated by more saline evaporitic paleoenvironmental conditions, possibly playa lakes or saline mudflats, as evidenced by δ 18 O values.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these dolomite-rich horizons near the coast, and the isotopic values of the dolomite, heavier than those of calcite suggest a source of water isotopically heavier than evolved meteoric water, such as seawater, similar to the described in the middle Devonian of Alberta (Williams and Krause, 1998), which also could supply the magnesium. The setting of formation of these dolomite-rich calcretes is different of those commonly described as a result of the evolution of groundwater to reach evaporitic conditions in terminal basin settings (Colson and Cojan, 1996;Jutras et al, 2011;Jutras, 2017) or as a result of the emerging groundwater also under evaporitic conditions (Mather et al, 2019). The scarce spheroidal dolomite found mostly cementing voids of the volcanic fragments is probably the first dolomite phase formed, as in Mirador del Rio profile in Lanzarote, where the initial weathering of the basalts could produce locally enriched Mg-solutions favoring dolomite formation (Capo et al, 2000;Whipkey et al, 2002;Whipkey and Hayob, 2008) as a cement (Alonso-Zarza et al, 2016).…”
Section: Calcrete Profiles Interpretationmentioning
confidence: 84%
“…The quasi-hypothetical model used in this study was inspired by lowland IRES encountered in arid northwest Australia (Cook & Dogramaci, 2019;Dogramaci et al, 2012Dogramaci et al, , 2015Mather et al, 2019;Tugwell-Wootton et al, 2020) and was conceptualized as a symmetrical V-shaped river-aquifer cross-section with an IRES at its center, flanked by a floodplain vegetated with riverine vegetation and underlain by a relatively conductive aquifer ( Figure 1). Owing to the symmetry of the cross-section, half-space could be simulated, and the computational burden significantly reduced.…”
Section: Conceptual Modelmentioning
confidence: 99%